Expert-Informed Hierarchical Diagnostics of Multiple Fault Modes of a Spacecraft Propulsion System - Aimiyekagbon, Osarenren Kennedy; Löwen, Alexander; Bender, Amelie; Muth, Lars; Sextro, Walter (Proceedings of the Asia Pacific Conference of the PHM Society 2023)
This paper presents a comprehensive study on diagnosing a spacecraft propulsion system utilizing data provided by the Prognostics and Health Management (PHM) society, specifically obtained as part of the Asia-Pacific PHM conference’s data challenge 2023. The objective of the challenge is to identify and diagnose known faults as well as unknown anomalies in the spacecraft’s propulsion system, which is critical for ensuring the spacecraft’s proper functionality and safety. To address this challenge, the proposed method follows a systematic approach of feature extraction, feature selection, and model development. The models employed in this study are kMeans clustering and decision trees combined to ensembles, enriched with expert knowledge. With the method presented, our team was capable of reaching high accuracy in identifying anomalies as well as diagnosing faults, resulting in attaining the seventh place with a score of 93.08 %.
Keywords: PHM; Fault Diagnostics; Multiple Fault Modes; Expert-Informed Diagnostics; Anomaly Detection

Pantalones Pariser Metamorphosen: Louis Riccobonis Observations sur la comédie et sur le génie de Molière - Steigerwald, Jörn (Zeitsprünge – Forschungen zur Frühen Neuzeit)

QMagFace: Simple and Accurate Quality-Aware Face Recognition - Terhörst, Philipp; Ihlefeld, Malte; Huber, Marco; Damer, Naser; Kirchbuchner, Florian; Raja, Kiran; Kuijper, Arjan (2023 IEEE/CVF Winter Conference on Applications of Computer Vision (WACV))

Explaining Face Recognition Through SHAP-Based Pixel-Level Face Image Quality Assessment - Biagi, Clara; Rethfeld, Louis; Kuijper, Arjan; Terhörst, Philipp (2023 IEEE International Joint Conference on Biometrics (IJCB))

Predicting the development of digital media PCK/TPACK: The role of PCK, motivation to use digital media, interest in and previous experience with digital media - Schubatzky, Thomas; Burde, Jan-Philipp; Große-Heilmann, Rike Isabel; Haagen-Schützenhöfer, Claudia; Riese, Josef; Weiler, David (Computers & Education)
Keywords: Education; General Computer Science

Pixel-Level Face Image Quality Assessment for Explainable Face Recognition - Terhörst, Philipp; Huber, Marco; Damer, Naser; Kirchbuchner, Florian; Raja, Kiran; Kuijper, Arjan (IEEE Transactions on Biometrics, Behavior, and Identity Science)
Keywords: Artificial Intelligence; Computer Science Applications; Computer Vision and Pattern Recognition; Instrumentation

PIC-Score: Probabilistic Interpretable Comparison Score for Optimal Matching Confidence in Single- and Multi-Biometric Face Recognition - Neto, Pedro C.; Sequeira, Ana F.; Cardoso, Jaime S.; Terhörst, Philipp (2023 IEEE/CVF Conference on Computer Vision and Pattern Recognition Workshops (CVPRW))

Uncertainty-aware Comparison Scores for Face Recognition - Huber, Marco; Terhörst, Philipp; Kirchbuchner, Florian; Kuijper, Arjan; Damer, Naser (2023 11th International Workshop on Biometrics and Forensics (IWBF))

QMagFace: Simple and Accurate Quality-Aware Face Recognition - Terhörst, Philipp; Ihlefeld, Malte; Huber, Marco; Damer, Naser; Kirchbuchner, Florian; Raja, Kiran; Kuijper, Arjan (Proceedings of the IEEE/CVF Winter Conference on Applications of Computer Vision (WACV))

Lorenz Jaeger als Person

Dokumente und Deutungen. Interpretationsprobleme anhand eines Fallbeispiels von sexuellem Kindesmissbrauch in Kärnten 1939 - Priesching, Nicole; Hartig, Christine (Kirchliche Macht und kindliche Ohnmacht. Konturen, Kontexte und Quellen theologischer Missbrauchsforschung)

Missbrauchsforschung als Thema der Zeitgeschichte - Priesching, Nicole; Kleinehagenbrock, Frank (Historisches Jahrbuch)

Individualization of Public Transport – Integration of Technical and Social Dimensions of Sustainable Mobility - Ostermann, Moritz; Behm, Jonathan; Marten, Thorsten; Tröster, Thomas; Weyer, Johannes; Cepera, Kay; Adelt, Fabian (Towards the New Normal in Mobility)
In order to follow the 1.5 degree path of the Paris Climate Agreement, drastic greenhouse gas reduction measures are needed in the transport sector. The potential of public transport and new mobility services to reduce transport-related greenhouse gas emissions cannot yet be fully exploited, especially in rural regions. This paper presents the concept of an innovative mobility system, called NeMo.bil, that intends to fill the gap between individual and public transport to create a demand-oriented and sustainable mobility offer. The concept is based on convoy formation of autonomously driving lightweight vehicles serving the first and last mile and a larger towing vehicle carrying enough power and energy to move the convoy over longer distances at higher speeds. This combination of two different vehicles, intelligently controlled by a digital ecosystem, aims to significantly increasing energy, resource and cost efficiency. Based on an analysis of previous approaches for innovative mobility solutions, the concept is derived from a technical and sociological perspective and its potential for reducing energy demand is calculated.

Introduction: Suffering and the Problem of Evil - Grössl, Johannes (T&T Clark Companion of Suffering and the Problem of Evil)

Der Gnadenstreit: Luis de Molina - Grössl, Johannes (Der Glaube im Denken. Eine Philosophiegeschichte)

The Impeccable Freedom of Christ - Grössl, Johannes (Theological Perspectives on Free Will: Compatibility, Community, Christology)

Zu den Anforderungen einer musikalischen Stilometrie - Kepper, Johannes
This is the extended abstract for my conference paper from the 2020 DHd Conference in Paderborn, along with the slides and moderator notes from the corresponding presentation.

DomesticBeethoven/bith-annotator: Release 2023-04 - Kepper, Johannes
This release covers the state of this prototype app at the end of the funding phase for the Paderborn University part of the Beethoven in the House project. It uses https://api.domestic-beethoven.eu/ld/BithCollection.jsonld as starting point for traversing the LOD graph, and reads data from the project pod available from https://bith.solidcommunity.net/public/bith.ttl (which has no content at the time of the release).
Keywords: MEI; Edirom; Music Encoding Initiative; Linked Open Data; MELD

MEI: The Music Encoding Initiative Guidelines (PDF)
PDF versions of the Music Encoding Initiative Guidelines 5.0 [2023]: This version represents the 5.0 release of the Music Encoding Initiative Guidelines.

Beethoven in the House: Selective Encodings of Arrangements of Beethoven’s opp. 91, 92, and 93. - Rosendahl, Lisa
This dataset contains selective MEI encodings of a number of arrangements of Beethoven’s Opp. 91, 92, and 93. These encodings were prepared in the context of the Beethoven in the House project, jointly funded by AHRC and DFG from 2020 to 2023. It is a slight update on v1.0.0 in better organizing the release assets.
Keywords: BitH; Dataset; Domestic Music Arrangements; Ludwig van Beethoven; MEI; Music Encoding Initiative